EFFECTIVENESS OF LAW ENFORCEMENT ON COLLECTING PUBLIC FUNDS ILLEGALLY USING INVESTMENT MODE - Fadhlilla Putri Ghaisani; DEborah Cecilia; Amanda Fidella Tryxie; Alisya Ivanna Insyira; Deborah Sondang R; Jessica Natanael. S; Adil Dwi Laksono (Zhata Institut, 2024)
Investment is all forms of investment activities, both by Domestic Investors and Foreign Investors, to conduct business in all sectors of the business sector in the territory of the Republic of Indonesia. This research aims to find out the law enforcement tekait the existence of funds collection in the community illegally with investment mode one of them Bodong Investment Rp. 1.3 T PT. Exist Assetindo. The existence of this bodong investment (illegal) has been troubling the wider community. This research uses descriptive qualitative research method is in the form of research with case study method or approach. The consequences of this illegal investment can lead to bodong or fictitious investments. With the activities of fund raising conducted by Limited Liability Companies, in addition to contrary to the provisions that have been regulated, it also hinders the existence of banking institutions. Given that the OJK has not provided regulations that specifically regulate the sanctions set for companies that collect funds illegally, the most basic legal policy applied is article 46 of Law No. 10 of 1998 on Banking.